The marine environment and oil facilities proceedings of a conference sponsored by the Society of Petroleum Engineers ... [et al.], organized by the Institution of Civil Engineers and held in London on 20 September, 1978. (Institution of Civil Engineers, 1979)
Following an opening address by A.M. Muir Wood, this work discusses the environmental impact of North Sea oil platforms, discusses sources and effects of hydrocarbons in the marine environment, as well as legislation for offshore facilities in the marine environment.